2019
DOI: 10.1002/prot.25677
|View full text |Cite
|
Sign up to set email alerts
|

All‐atom structure ensembles of islet amyloid polypeptides determined by enhanced sampling and experiment data restraints

Abstract: Exploring the accurate structure ensembles are critical to understand the functions of intrinsically disordered proteins (IDPs). As a well‐known IDP, islet amyloid polypeptide (IAPP) plays important roles in the development of human type II diabetes (T2D). The toxicity of human IAPP (hIAPP) is induced by the amyloidosis of the peptide, however, its aggregation mechanism remains ambiguous. The characterization of structure ensemble of hIAPP, as well as the differences between hIAPP and its non‐amyloidogenic hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…A single molecule of IAPP has been simulated in the presence of a lipid bilayer [302][303][304] or without membrane to compare the monomeric state of hIAPP and pIAPP 305 or rIAPP. 306 In µs-long MD simulations Qiao et al observed transient α-helical and β-sheet structure of monomeric hIAPP during adsorption to the surface of a POPG (palmitoyloleoyl phosphatidylglycerol) bilayer. 304 The hIAPP adsorption caused bending of the POPG bilayer and hydrophobic irregularities.…”
Section: Simulations Of Monomeric Iapp and Interactions With Lipid Membranementioning
confidence: 99%
See 1 more Smart Citation
“…A single molecule of IAPP has been simulated in the presence of a lipid bilayer [302][303][304] or without membrane to compare the monomeric state of hIAPP and pIAPP 305 or rIAPP. 306 In µs-long MD simulations Qiao et al observed transient α-helical and β-sheet structure of monomeric hIAPP during adsorption to the surface of a POPG (palmitoyloleoyl phosphatidylglycerol) bilayer. 304 The hIAPP adsorption caused bending of the POPG bilayer and hydrophobic irregularities.…”
Section: Simulations Of Monomeric Iapp and Interactions With Lipid Membranementioning
confidence: 99%
“…Su et al have analyzed the monomeric state of hIAPP and rIAPP in solution (without membrane) by metadynamics sampling. 306 The enhanced sampling results were carried out separately with and without NMR chemical shift restraints, and compared to unbiased sampling.…”
Section: Scollo Et Al Investigated Hiapp Insertion In a Popc (Phosphatidylcholine) Bilayer Bymentioning
confidence: 99%
“…However, additional experimental data are needed to propose more accurate models depicting the role of exosomes in IAPP amyloidogenesis and diabetes development. Molecular simulations of membrane-bound hIAPP from different species have been carried out [200][201][202] including the non-toxic, non-amyloidogenic rIAPP [203]. Molecular dynamics (MD) simulations revealed short-lived α-helical and β-sheet structures throughout IAPP adsorption onto an anionic POPG (palmitoyl oleoyl phosphatidylglycerol) surface of a lipid bilayer [201].…”
Section: Iapp-membrane Interactionsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] The ensemble of IDPs contains a vast number of diverse conformations, and ligands bind to IDPs via dynamic and transient interactions. [30][31][32][33] In other words, the apparent binding affinity between a ligand and an IDP is a result of ensemble averaging. In statistical mechanics, it is well known that the large number of degree of freedom does not complicate the situation, but actually greatly simplifies the results (e.g., to result in Boltzmann distribution).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have long been recognized as attractive therapeutic targets, 18–21 and great efforts have been made to develop drugs targeting IDPs 22–29 . The ensemble of IDPs contains a vast number of diverse conformations, and ligands bind to IDPs via dynamic and transient interactions 30–33 . In other words, the apparent binding affinity between a ligand and an IDP is a result of ensemble averaging.…”
Section: Introductionmentioning
confidence: 99%